PENENTUAN LOKASI ATM BANK SYARIAH INDONESIA MENGGUNAKAN METODE FUZZY C MEANS DI KABUPATEN JEMBER - kiswara santoso; Amalia Nur Azizah (Jurnal Matematika Sains dan Teknologi, 2022)
Bank Syariah Indonesia was inaugurated on February 1, 2021, which is a combination of BNI Syariah, Mandiri Syariah, and BRI Syariah. One of the ease of transaction facilities for customers is using an ATM (Automated Teller Machine). BSI currently has 18,291 ATMs spread throughout Indonesia and 10 of them are located in Jember Regency. The purpose of the ATM is to increase customer convenience and public trust in BSI. Ease of access to ATMs will affect the number of customers because ATM locations that are easily accessible can increase the number of profits obtained by BSI. The main factors in determining the location of ATMs that need to be considered are easy to reach, close distances, and safe locations. The Fuzzy C Means (FCM) method is used to classify the right area in determining the location of ATMs. The results of this study, the Jember district can be grouped into 6 clusters, wherein each cluster there is one ATM with the first cluster and the sixth cluster with as many as 9 districts, the second cluster with as many as 6 districts, the third cluster as many as 5 districts, the fourth cluster as many as 7 districts, and the fifth cluster as many as 4 districts. The conclusion of this study, is the exact location of BSI ATMs in Jember Regency based on the number of clusters that have been determined to be in Patemon Village, Antirogo Village, Jubung Village, Jember Lor Village, and Sumbersari Village. Clustering validation uses the Silhoutte Index (SI) with an average silhouette coefficient of 0.83028.